Kinetics and crystallization path of a Fe-based metallic glass alloy. (1st April 2017) - Duarte, M.J.; Kostka, A.; Crespo, D.; Jimenez, J.A.; Dippel, A.-C.; Renner, F.U.; Dehm, G.
Abstract: The thermal stability and the quantification of the different transformation processes involved in the overall crystallization of the Fe50 Cr15 Mo14 C15 B6 amorphous alloy were investigated by several characterization techniques. Formation of various metastable and stable phases during the devitrification process in the sequence α-Fe, χ-Cr6 Fe18 Mo5, M23 (C, B)6, M7 C3, η-Fe3 Mo3 C and FeMo2 B2 (with M = Fe, Cr, Mo), was observed by in-situ synchrotron high energy X-ray diffraction and in-situ transmission electron microscopy. By combining these techniques with differential scanning calorimetry data, the crystallization states and their temperature range of stability under continuous heating were related with the evolution of the crystallized fraction and the phase sequence as a function of temperature, revealing structural and chemical details of the different transformation mechanisms. Graphical abstract: Image 1